The Concept of Intellectual Property As Al Mal: An Islamic Perpective Approach - Mohd Izzat Amsyar Mohd Arif; Hisham Hanapi (International Journal of Educational Best Practices, 2017)
The idea of legally acknowledging and protecting the intellectual property is prevalently known inany legal system in the world, but not many people know how this idea is dealt in Islam. Islam asthe religion of wholeness (syumul), deals with almost all aspects of life and aims at protecting fivemain objectives of syariah3 (maqasid al syariah) namely religion (al din), life (al nafs), intellect(al aqal), lineage (al nasl) as well as property (al mal). As the time goes by, people started torealize that human intelligence and creativity shall not be the object of manipulation, thusnecessitated them to come up with some sort of protection for their invention by legallyacknowledging it as ‘intellectual property’. This paper will try to discuss the position of intellectualproperty in the Islamic jurisprudence by determining its ‘maaliyyah’ (capable of being consideredas property).